THE COMPARATIVE STUDY OF REPRODUCTION PARAMETERS FOR CHINCHILLA LANIGER - C.D. CĂLĂMAR (Scientific Papers Animal Science and Biotechnologies, 2013)
The study was made in 2007 on 500 females of Chinchilla,kept in individual cages, with a passage for the male. The next parameters were established based on reproduction results: prolificity index (PI), sex ratio, offspring survival index (OSI), female usage index (FUI). Based on these parameters, the fertility index has been calculated,during two births. For the first birth, the fertility index was 4.22 offsprings/female, for the second birth, it was 3.65 offsprings/female.